A Heuristic Approach for Inter-Facility Comparison of Results from Round Robin Testing of a Floating Wind Turbine in Irregular Waves - Sebastien Gueydon; Frances Judge; Eoin Lyden; Michael O’Shea; Florent Thiebaut; Marc Le Boulluec; Julien Caverne; Jérémy Ohana; Benjamin Bouscasse; Shinwoong Kim; Sandy Day; Saishuai Dai; et al. (Journal of Marine Science and Engineering, 2021)
This paper introduces metrics developed for analysing irregular wave test results from the round robin testing campaign carried out on a floating wind turbine as part of the EU H2020 MaRINET2 project. A 1/60th scale model of a 10 MW floating platform was tested in wave basins in four different locations around Europe. The tests carried out in each facility included decay tests, tests in regular and irregular waves with and without wind thrust, and tests to characterise the mooring system as well as the model itself. While response amplitude operations (RAOs) are a useful tool for assessing device performance in irregular waves, they are not easy to interpret when performing an inter-facility comparison where there are many variables. Metrics that use a single value per test condition rather than an RAO curve are a means of efficiently comparing tests from different basins in a more heuristic manner. In this research, the focus is on using metrics to assess how the platform responds with varying wave height and thrust across different facilities. It is found that the metrics implemented are very useful for extracting global trends across different basins and test conditions.

Round Robin Laboratory Testing of a Scaled 10 MW Floating Horizontal Axis Wind Turbine - Sebastien Gueydon; Frances M. Judge; Michael O’Shea; Eoin Lyden; Marc Le Boulluec; Julien Caverne; Jérémy Ohana; Shinwoong Kim; Benjamin Bouscasse; Florent Thiebaut; Sandy Day; Saishuai Dai; et al. (Journal of Marine Science and Engineering, 2021)
This paper documents the round robin testing campaign carried out on a floating wind turbine as part of the EU H2020 MaRINET2 project. A 1/60th scale model of a 10 MW floating platform was tested in wave basins in four different locations around Europe. The tests carried out in each facility included decay tests, tests in regular and irregular waves with and without wind thrust, and tests to characterise the mooring system as well as the model itself. For the tests in wind, only the thrust of the turbine was considered and it was fixed to pre-selected levels. Hence, this work focuses on the hydrodynamic responses of a semi-submersible floating foundation. It was found that the global surge stiffness was comparable across facilities, except in one case where different azimuth angles were used for the mooring lines. Heave and pitch had the same stiffness coefficient and periods for all basins. Response Amplitude Operators (RAOs) were used to compare the responses in waves from all facilities. The shape of the motion RAOs were globally similar for all basins except around some particular frequencies. As the results were non-linear around the resonance and cancellation frequencies, the differences between facilities were magnified at these frequencies. Surge motions were significantly impacted by reflections leading to large differences in these RAOs between all basins.

Wave Energy Converter Power Take-Off System Scaling and Physical Modelling - Gianmaria Giannini; Irina Temiz; Paulo Rosa-Santos; Zahra Shahroozi; Victor Ramos; Malin Göteman; Jens Engström; Sandy Day; Francisco Taveira-Pinto (Journal of Marine Science and Engineering, 2020)
Absorbing wave power from oceans for producing a usable form of energy represents an attractive challenge, which for the most part concerns the development and integration, in a wave energy device, of a reliable, efficient and cost-effective power take-off mechanism. During the various stages of progress, for assessing a wave energy device, it is convenient to carry out experimental testing that, opportunely, takes into account the realistic behaviour of the power take-off mechanism at a small scale. To successfully replicate and assess the power take-off, good practices need to be implemented aiming to correctly scale and evaluate the power take-off mechanism and its behaviour. The present paper aims to explore and propose solutions that can be applied for reproducing and assessing the power take-off element during experimental studies, namely experimental set-ups enhancements, calibration practices, and error estimation methods. A series of recommendations on how to practically organize and carry out experiments were identified and three case studies are briefly covered. It was found that, despite specific options that can be strictly technology-dependent, various recommendations could be universally applicable.

Numerical Modelling of the Nearfield Longitudinal Wake Profiles of a High-Speed Prismatic Planing Hull - Angus Gray-Stephens; Tahsin Tezdogan; Sandy Day (Journal of Marine Science and Engineering, 2020)
This study investigates the level of accuracy with which Computational Fluid Dynamics (CFD) is capable of modelling the nearfield longitudinal wake profiles of a high-speed planing hull. It also looks to establish how various set-ups influence the accuracy, with a specific emphasis on turbulence modelling. It analyses a hull over a broad range of conditions to provide detailed insight into the strengths and limitations of CFD, comparing the numerical results to the experimental results previously generated by the authors. A quantitative comparison is made for the centreline (CL) and quarterbeam (QB) longitudinal wake profile plots. Following this, a qualitative comparison is made between photos of the flow pattern from the experimental testing and free surface elevation plots from CFD. The study concluded that CFD is an accurate and robust method of modelling the nearfield longitudinal wake profiles of a high-speed planning hull.

Results of FDA’s First Interlaboratory Computational Study of a Nozzle with a Sudden Contraction and Conical Diffuser - Sandy F. C. Stewart; Prasanna Hariharan; Eric G. Paterson; Greg W. Burgreen; Varun Reddy; Steven W. Day; Matthew Giarra; Keefe B. Manning; Steven Deutsch; Michael R. Berman; Matthew R. Myers; Richard A. Malinauskas (Cardiovascular Engineering and Technology, 2013)

Assessment of CFD Performance in Simulations of an Idealized Medical Device: Results of FDA’s First Computational Interlaboratory Study - Sandy F. C. Stewart; Eric G. Paterson; Greg W. Burgreen; Prasanna Hariharan; Matthew Giarra; Varun Reddy; Steven W. Day; Keefe B. Manning; Steven Deutsch; Michael R. Berman; Matthew R. Myers; Richard A. Malinauskas (Cardiovascular Engineering and Technology, 2012)